The Role of the International Economic Organizations and the Public Sector in Creating and Sustaining International Competitiveness - Irina-Elena Gentimir (CES Working Papers, 2013)
By analyzing the global economy, one can easily notice that states that record economic growth are competitive, and that the competitive ones collect revenues of billions of dollars from trade, outsourcing and meeting the needs of their citizens. The role of private sector in creating and sustaining competitiveness it is well known. But what actions are undertaken by the international organizations and the public sector in this direction? The scope of this article is to offer a brief description of the role played by these actors taking into account that they must create the fundamental condition for competitiveness: macroeconomic stability.
Keywords: F00; E00; 330; public sector; international organizations; international competitiveness Romania